Supervivencia de implantes dentales en pacientes con infección por VIH - Ponce Marón, Pamela (2021)
Objective: To identify the survival rate of dental implants in patients with human immunodeficiency virus (HIV) infection. Material and methods: An electronic search was carried out for observational and experimental studies published up to march 2021 in the PubMed, PubMed Central, Cochrane databases and in the journals about periodontics and implants with a high impact factor according to ISI Web of Science. The assessment of the risk of bias of the observational articles was assessed using the Newcastle-Ottawa scale and the Cochrane manual Version 5.1.0 for clinical trials. Results: 8 observational studies, 2 case reports, 5 case series and 1 cohort study were found, with a follow-up of 1 to 12 years. A total of 1033 dental implants were placed, the CD4+ lymphocyte count presented a mean of 531.48 mm3. The dental implant survival rate in HIV positive patients was 95.31 %. According to the Newcastle Ottawa scale, all included articles showed a low risk of bias. Conclusion: The present systematic review showed a 95.31 % dental implant survival rate in HIV positive patients with a follow-up time of 1 to 12 years.